Kebijakan Pendidikan dan Pengembangan Intelektualitas pada Masa Harun Ar-Rasyid (786 - 809 M) - Febriyan, Dio; Arifin, Faizal (Historia Madania: Jurnal Ilmu Sejarah, 2025)
This study examines the significant role played by Harun Ar-Rashid, the fifth caliph of the Abbasid Dynasty, in advancing education during his reign. Employing historical research methods, including heuristics, source criticism, interpretation, and historiography, the research relies primarily on The History of Al-Tabari as a key source. The analysis reveals notable progress in education during Harun Ar-Rashid's Caliphate, attributing the Abbasid Dynasty's advancement to his educational policies. Initiatives such as the establishment of translation institutions, multiple libraries, and the integration of the Qur'an as a core curriculum contributed to this progress. Renowned scholars like Al-Khawarizmi, Al-Kindi, Ar-Raji, and Al-Ma’mun emerged due to these policies. Harun Ar-Rashid's proactive programs aimed at enhancing educational accessibility and fostering a love for science have enduring implications. If applied in contemporary education, these policies could contribute to equalizing educational quality. This article explores the historical roots of these initiatives, offering insights for present-day educational strategies and contributing to the discourse on educational equality. By understanding the legacy of Harun Ar-Rashid's educational efforts, we gain perspectives to guide modern endeavors in creating inclusive and effective educational systems.